Old arguments, new challenges: public policies and the anti-vax movement (Research, Society and Development, 2021)
The existence of challenges to public immunization policies imposed by scientific denialism is not new. In the history of Brazil, it is observed that the anti-vax movement has existed since the 19th century, based on fallacious justifications that have discredited science by the most different legal, moral, and religious arguments. This article aims to interpret the refutation of public policies to combat the coronavirus pandemic under the events that resulted in the Vaccine Revolt. To this end, a narrative literature review was conducted, outlined by searching for scientific articles and bibliographies in the main international electronic repositories. The descriptors used for the search were: vaccines, COVID-19, immunization, history, sanitary measures, denialism, anti-vax movements, and Brazil. A line of continuity was perceived between past and present discourses opposing restrictive measures and vaccination, either by claiming to defend individual freedom or by invoking obscurantist ideas. We have concluded that the arbitrary refusal to comply with public health policies constitutes an abusive exercise against the right to individual freedom, by exposing society to serious and avoidable risks.